Regional burden of Anemia among Adolescent girls in India: A systematic review and meta-analysis - Kumari, Anita; Kumari, Amita; Mudgal, Shiv Kumar; Patidar, Vipin; Singh, Abhishek Kumar; Ganguly, Abhimanyu; Singh, Sanjeet Kumar (Nepal Journal of Epidemiology, 2025)
Background: Among Indian adolescent girl’s anemia remains a major public health concern due to rapid growth, menstrual blood loss, and nutritional deficiencies. This systematic review and meta-analysis aim to assess the prevalence and severity of anemia among Indian adolescent girls.Methods: This review (2004–2024) integrated data from 32 studies (14,053 persons) from PubMed, Embase, and Scopus, adhering to Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA)/ Meta-analysis Of Observational Studies in Epidemiology (MOOSE) guidelines. Observational studies with the prevalence of anemia in Indian adolescent girls based on WHO criteria were included. The data was pooled using a random-effects model, and subgroup analyses were conducted by Indian region. Heterogeneity was assessed using the I2 statistic.Results: The pooled anemia prevalence was 65% (95% CI: 54%–74%), showed notable regional variations. The burden was highest in East India (81%; 39%–97%), then North India (65%), West India (61%), and South India (52%). The mean hemoglobin levels varied by region, ranging from 10.24 g/dL in the East to 11.20 g/dL in the South. Mild anemia (29%) and moderate anemia (25%) were more common than severe anemia (1%). The substantial heterogeneity (I2=98.7%) indicated differences in socioeconomic status, diet, and healthcare access.Conclusion: Anemia affects disproportionate number of Indian adolescents’ girls, particularly in the country's east, which highlights the need for context-specific interventions. The initiatives must be linked to national programs like Anemia Mukt Bharat to ensure equitable progress towards India's public health objectives and to avoid long-term health and developmental consequences.